U. S. Spacesuits - Thomas, Kenneth S.; McMann, Harold J.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Spacesuits are far more than garments. They are a personalized spacecraft that allows direct contact and interaction with everything beyond our world, and a last refuge for survival in a disaster. Creating safe, reliable, and comfortable spacesuits is an ongoing challenge that has spanned over four decades. "U. S. Spacesuits, 2nd Edition" by Kenneth S. Thomas and Harold J. McMann details the technical evolution of U. S. spacesuits from their roots in high altitude aviation and vacuum tube development to present day, with an additional look into the future. This primary source of spacesuit information explains the functions, historical development, and use of spacesuits from a worldwide perspective. In this new edition, the authors update the story of U.S. spacesuit development and efforts, from the design challenges modern engineers face to the latest roles of spacesuits in space exploration. The book also provides a close up look at NASA's new Constellation Space Suit System as well as Apollo prototype configurations that have been discovered since 2005. Also not in the earlier edition is a prototype and model of the Gemini pressure suit and an explanation of its development. Finally, there are new insights into the suits used for the Gemini, Apollo, Skylab, Space Shuttle, and International Space Station missions.
List of figures -- List of tables -- List of contributors -- Preface -- Foreword -- Acknowledgments -- Editorial notes -- Acronyms and abbreviations -- Chapter 1: Introduction -- Chapter 2: Reaching upward and outward -- Chapter 3: The basics of spacesuits -- Chapter 4: Launch/entry spacesuits: Past, present, and possibly future -- Chapter 5: Gemini: The first approaches to exploring and working in space -- Chapter 6: Apollo: Mankind starts the exploration of the Moon -- Chapter 7: Advanced development for canceled Apollo missions -- Chapter 8: U.S. Air Force spacesuits -- Chapter 9: Skylab and the Apollo-Soyuz Test Project suit systems (1969-1975) -- Chapter 10: The Space Shuttle program: Orbital EVA comes of age -- Chapter 11: The quest for future extravehicular activity and planetary exploration -- Chapter 12: Epilogue -- Appendix A: U.S. spaceflight suit system overview -- Appendix B: U.S. EVA information -- Bibliography -- Index.
Keywords: Physics; Astrophysics; Astronomy; Astronautics; Physics; Extraterrestrial Physics, Space Sciences; Popular Science in Astronomy; Aerospace Technology and Astronautics